Gαi1 promotes migration of epidermal cells exposed to short-term hypoxia - ZHOU Xin; HUANG Jingzhuo; CHEN Xin; MAO Tongchun; LI Xiang; YAN Rongshuai (Di-san junyi daxue xuebao, 2019)
Objective To investigate the changes in the migration and motility of epidermal cells cultured under hypoxic conditions and the role of Gαi1 in promoting these changes. Methods A workstation for live cell imaging was used to observe the changes in the migration and motility of HaCaT cells cultured under hypoxic conditions for 24 h in comparison with cells in routine culture. Microarray chip technique was used to screen the differentially expressed genes that participated in the regulation of cell migration early after hypoxia exposure; Western blotting, immunofluorescence assay and lentivirus-mediated siRNA transfection were used to explore the role of Gαi1 protein in regulating the migration of HaCaT cells under hypoxic conditions. Results The migration ability of HaCaT cells was significantly enhanced under hypoxic conditions, and their movement rate and movement persistence were increased obviously early after hypoxic exposure (in the first 12 h) compared with the cells in normoxic culture. Western blotting and immunofluorescence assay showed that the exposure to hypoxia caused over-expression of Gαi1 protein in HaCaT cells. RNA interference of Gαi1 protein significantly lowered the migration ability of the cells irrespective of normoxic and hypoxic exposures and also resulted in obviously lowered cell motility and movement persistence. Conclusion Short-term hypoxic exposure significantly enhances the migration and movement of epidermal cells, and Gαi1 protein plays an important role in promoting the migration of epidermal cells under hypoxia.